Study to Assess Outcome After Open and Closed Carpal Tunnel Decompression. Issue 5 (November 2015) - Akhtar, Sohail; Bradley, Mary J.; Burke, Frank D.; Dubin, Norman H.; Wilgis, E.F. Shaw
Abstract : Abstract: Carpal tunnel decompression (CTD) is the most commonly performed surgical procedure within a hand unit. We have analyzed data on outcomes after carpal decompression performed by both open and closed techniques to assess whether outcomes differed between the 2 procedures. Data were jointly gathered from 2 units. The aim was to assess the outcome after CTD. Completed data were gathered from 621 CTD procedures performed on 484 patients. Of the procedures, 358 were performed via a standard open CTD technique and 263 procedures were performed via a closed single-port Agee technique. Assessments were performed by means of the Levine-Katz questionnaire, Semmes-Weinstein monofilament testing, grip strength, and pinch-grip strength testing. Assessments were performed both preoperatively and 6 months postoperatively. A randomly selected 10% of patients were also assessed at 12 months. The results were statistically better after closed CTD at the 6-month postoperative stage. However, the difference became less marked by 12-month postoperative stage. Our results show that CTD whether performed by an open or closed technique resulted in a similar outcome at the 12-month postoperative stage. However, those procedures performed by a closed technique offered a more rapid recovery in the first 6 months postoperative than by an open technique.